Cowchock Wapner Kurtz Syndrome: Giant and Lethal Neck Cystic Hygroma: A Case Report - Avina Fierro JA; Hernandez Avina DA (Global Journal of Rare Diseases - Peertechz Publications, 2017)
Cowchock Wapner Kurtz syndrome is a very rare disease and lethal disorder with cervical lymphangioma obstructing the airway and causing complications, with accelerated growth resembling a teratoma. We report a 21-month-old infant with a congenital giant neck cystic hygroma, cleft palatal and deformation of the surrounded area by lymphedema and tissue swelling; started with respiratory compromise because the expansion of the malformation, requiring repetitive surgeries without remission, showing recurrence and accelerated growth of the mass. It was used sclerotherapy with Picibanil, without satisfactory response; the patient suffered a rapid deterioration and dead. This is a rare syndrome of genetic etiology currently not clarified; apparently from healthy parents, and patient's karyotype normal, maybe can be a micro deletion that only could be detected using advanced cytogenetics.